Analisis Iddentifikasi Modul Baseband Sebagai Layanan Jaringan 4G-LTE pada Perangkat BBU di Wilayah Kota Malang - Nilam Hanifa Nur Rahmadzani (Politeknik Negeri Malang, 2019)
Constraints related to 4G technology are the unequal areas covered so that users who want to experience the 4G network have to go to a point that is already covered. The research objective is to determine the benefits of existing BTS by replacing the baseband module which can add 4G network services and knowing how to choose the type of baseband module and knowing how to do a drivetest related to 4G network service coverage in the planning area. The method used is Calculation of capacity planning and throughput calculations to determine the condition of the planning area before replacing the baseband module at the specified site. The condition of the existing site in the planning area has not changed because only the baseband module is replaced in the existing site. Calculation based on capacity planningshows the total number of active users 900 users, while the network throughput shows the uplink value of 8.56 Mbps and downlink of 32.74 Mbps. Drivetest measurements are carried out to determine whether the performance value has met the planning. Based on the data from the drivetest results, the RSRP value is 99% and the distribution of the RSRP value is in the range of -92 dBm which means that it is very good. Meanwhile, the SINR value of 52.6% is in the 5 Db range, which means good. For the measurement of the speedtest, the download speed is 134 Mbps and the upload is 40 Mbps.